The Effect of Earthworm (Lumbricus terrestris L.) Population Density and Soil Water Content Interactions on Nitrous Oxide Emissions from Agricultural Soils - Andrew K. Evers; Tyler A. Demers; Andrew M. Gordon; Naresh V. Thevathasan (Applied and Environmental Soil Science)
Earthworms may have an influence on the production of N2O, a greenhouse gas, as a result of the ideal environment contained in their gut and casts for denitrifier bacteria. The objective of this study was to determine the relationship between earthworm (Lumbricus terrestris L.) population density, soil water content and N2O emissions in a controlled greenhouse experiment based on population densities (90 to 270 individuals m−2) found at the Guelph Agroforestry Research Station (GARS) from 1997 to 1998. An experiment conducted at considerably higher than normal densities of earthworms revealed a significant relationship between earthworm density, soil water content and N2O emissions, with mean emissions increasing to 43.5 g ha−1day−1 at 30 earthworms 0.0333 m−2 at 35% soil water content. However, a second experiment, based on the density of earthworms at GARS, found no significant difference in N2O emissions (5.49 to 6.99 g ha−1day−1) aa a result of density and 31% soil water content.